Personal Responsibility Relationship to Environmental Responsibility Behavior - Ni Ketut Suzana Ayu Apriani Wirawan (Green Publisher Indonesia, 2022)
This research discusses the role of an international organization called Junior Chamber International (JCI) in Indonesia which helps the provision and management of clean water and sanitation as one of the realizations of the global sustainable development goals (SDGs) in Indonesia. This study uses a qualitative approach with case study research methods. Data was collected by interviewing several relevant sources and observing various JCI activities. Other data were obtained from secondary data in the form of literature studies and various supporting documentation such as books and journals, data from the Central Statistics Agency (BPS) and the DKI Provincial Government, as well as the results of periodic reports and various photo documentation of JCI's activities. Liberalism theory was chosen as an approach that is considered capable of providing answers to the positive changes formed and carried out by JCI in international relations cooperation to realize sustainable development. The results of the study show that JCI as an international organization is a platform for young professionals in their fields and can directly contribute in depth. JCI is also able to navigate the interests of stakeholders both towards the government, NGOs, other international organizations, and the community as targets in terms of efforts to realize the six sustainable development goals, namely the management and provision of access to clean water and sustainable sanitation